Dextran Sulphate Sodium Acute Colitis Rat Model: A Suitable Tool for Advancing Our Understanding of Immune and Microbial Mechanisms in the Pathogenesis of Inflammatory Bowel Disease - Petra Adamkova; Petra Hradicka; Helena Kupcova Skalnikova; Veronika Cizkova; Petr Vodicka; Silvia Farkasova Iannaccone; Monika Kassayova; Sona Gancarcikova; Vlasta Demeckova (Veterinary Sciences, 2022)
Inflammatory bowel disease (IBD) is a group of disorders causing inflammation in the digestive tract. Recent data suggest that dysbiosis may play a pivotal role in the IBD pathogenesis. As microbiome-based therapeutics that modulate the gut ecology have been proposed as a novel strategy for preventing IBD, the aim of presenting study was to evaluate the dextran sulphate sodium (DSS) rat model mainly in terms of microbial shifts to confirm its suitability for dysbiosis study in IBD. Acute colitis was induced using 5% DSS solution for seven days and rats were euthanized five days after DSS removal. The faecal/caecal microbiota was analyzed by next generation sequencing. Disease activity index (DAI) score was evaluated daily. Blood and colon tissue immunophenotyping was assessed by flow cytometry and histological, haematological, and biochemical parameters were also evaluated. The colitis induction was reflected in a significantly higher DAI score and changes in all parameters measured. This study demonstrated significant shifts in the colitis-related microbial species after colitis induction. The characteristic inflammation-associated microbiota could be detected even after a five day-recovery period. Moreover, the DSS-model might contribute to an understanding of the effect of different treatments on extraintestinal organ impairments. The observation that certain bacterial species in the gut microbiota are associated with colitis raises the question of whether these organisms are contributors to, or a consequence of the disease. Despite some limitations, we confirmed the suitability of DSS-induced colitis model to monitor microbial changes during acute colitis, in order to test attractive new microbiome-based therapies.